(untitled) (Scientia Agricola, 2001)
Ten P fertilizers were collected (commercial fertilizers) or synthesized (experimental sources) in order to obtain single superphosphates varying in water and citrate solubility. A standard source of P was also produced by crystallization of the water-soluble fraction of a triple superphosphate. Eleven P sources were band applied to a medium textured Xanthic Hapludox, in Bahia, Brazil (low content of resin-extractable P) at a rate of 80 kg ha-1 of NAC + H2O (neutral ammonium citrate plus water) soluble P2O5, with soybean as the crop which was grown to maturity. A check plot (control) was included in the study. Three of the P sources [single superphosphate produced from Araxa phosphate rock (PR), low-grade single superphosphate produced from Lagamar PR and the standard source of P] were also applied at rates to provide 40 and 120 kg ha-1 of NAC + H2O soluble P2O5. Yield of soybean was evaluated by analysis of variance with mean comparison performed utilizing LSD lines, considering the P sources applied at a rate of 80 kg ha-1 of P2O5 + control. Regression procedures were used to study the relation between yield of soybean and rates of P2O5. The fertilizers tested performed equally well as a source of P for soybean. The level of water-soluble P did not influence fertilizer performance.